PENGEMBANGAN BOOKLET BERBASIS RADEC PADA MATERI STRUKTUR ATOM SMK - Nirmatya; Syolendra, Dwi Finna (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Chemistry is a branch of science that studies the composition, structure, characteristics, and changes of matter, including the energy associated with those changes. However, most of its concepts are abstract, making them difficult for students to understand, especially in the topic of atomic structure. Based on the quiz results of phase E students at SMK SMAK Padang, 63.89% did not achieve the minimum mastery score. This issue indicates the need for engaging, communicative, and varied learning materials to support students’ understanding, as the current materials are mostly limited to textbooks. This study aims to develop teaching material in the form of a booklet based on the RADEC model (Read, Answer, Discuss, Explain, and Create) that is valid and practical for the atomic structure topic in vocational high schools. The research employed the Research and Development (R&D) method using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The validation results show that the booklet meets the validity criteria, with Aiken’s V scores of 0.91 for content, 0.91 for language, and 0.89 for graphics. The practicality test indicates that the booklet falls into the very practical category, with an average score of 84% from teachers and 93% from students. In terms of ease of use, the booklet achieved an average of 86% from teachers and 93% from students, both categorized as very practical. The efficiency aspect obtained averages of 80% from teachers and 90% from students, while the usefulness aspect scored 87% from teachers and 95% from students, all of which are categorized as practical to very practical. It can be concluded that the RADEC-based booklet on atomic structure material can be developed using the ADDIE model and has met the criteria of validity and practicality, making it feasible to be used as teaching material. ABSTRAKKimia merupakan cabang ilmu sains yang mempelajari susunan, struktur, karakteristik, serta perubahan materi, termasuk energi yang terkait dengan perubahan tersebut. Namun, sebagian besar konsepnya bersifat abstrak sehingga sulit dipahami peserta didik, khususnya pada materi struktur atom. Berdasarkan hasil kuis peserta didik fase E SMK SMAK Padang, sebanyak 63,89% tidak mencapai nilai ketuntusan. Permasalahan ini menunjukkan perlu adanya bahan ajar yang menarik, komunikatif, dan variatif untuk membantu pemahaman peserta didik, karena bahan ajar yang digunakan saat ini dominan pada buku paket. Penelitian ini bertujuan untuk mengembangkan bahan ajar berupa booklet berbasis RADEC (Read, Answer, Discuss, Explain, and Create) yang valid dan praktis pada materi struktur atom SMK. Penelitian menggunakan metode Research and Development (R&D) dengan model ADDIE (Analyze, Design, Develop, Implement, Evaluate). Instrumen penelitian terdiri dari lembar validasi dan angket praktikalitas. Hasil validasi menunjukkan bahwa booklet memenuhi kriteria valid dengan nilai rata-rata Aiken’s V sebesar 0,91 yang mencakup aspek isi sebesar 0,91, aspek kebahasaan 0,91, dan aspek kegrafisan 0,89. Uji praktikalitas booklet berada pada kategori sangat praktis, dengan rata-rata 84% dari guru dan 93% dari peserta didik yang mencakup aspek kemudahan penggunaan, diperoleh rata-rata 86% dari guru dan 93% dari peserta didik dengan kategori sangat praktis. Aspek efisiensi waktu menunjukkan rata-rata 80% dari guru dan 90% dari peserta didik, sedangkan aspek manfaat memperoleh rata-rata 87% dari guru dan 95% dari peserta didik, seluruhnya berada pada kategori praktis hingga sangat praktis. Dapat disimpulkan bahwa booklet berbasis RADEC pada materi struktur atom dapat dikembangkan dengan model ADDIE dan telah memenuhi kriteria valid dan praktis sehingga layak digunakan sebagai bahan ajar.